Short‐term mudflat dynamics drive long‐term cyclic salt marsh dynamics. (3rd August 2016) - Bouma, T. J.; van Belzen, J.; Balke, T.; van Dalen, J.; Klaassen, P.; Hartog, A. M.; Callaghan, D. P.; Hu, Z.; Stive, M. J. F.; Temmerman, S.; Herman, P. M. J.
Abstract: Our study aims to enhance process understanding of the long‐term (decadal and longer) cyclic marsh dynamics by identifying the mechanisms that translate large‐scale physical forcing in the system into vegetation change, in particular ( i) the initiation of lateral erosion on an expanding marsh, and ( ii) the control of seedling establishment in front of an eroding marsh‐cliff. Short‐term sediment dynamics (i.e., seasonal and shorter changes in sediment elevation) at the mudflat causes variation in mudflat elevation over time ( δ zTF ). The resulting difference in elevation between the tidal flat and adjacent marsh (Δ Z ) initiates lateral marsh erosion. Marsh erosion rate was found to depend on sediment type and to increase with increasing Δ Z and hydrodynamic exposure. Laboratory and field experiments revealed that seedling establishment was negatively impacted by an increasing δ zTF . As the amplitude of δ zTF increases towards the channel, expanding marshes become more prone to lateral erosion the further they extend on a tidal flat, and the chance for seedlings to establish increases with the distance that marsh has eroded back towards the land. This process‐based understanding, showing the role of sediment dynamics as explanatory factor for marsh cyclicity, is important for protecting and restoring valuable marsh ecosystems. Overall, our experiments emphasize the need for understanding the connections between neighbouring ecosystems such as mudflat and salt marsh.